The Right To Make Corrections And The Right To Reply Under The Press Law - Drgonec, Ján (Communication Today, 2025)
The right to make corrections and the right to reply – in some countries are these rights protected by their constitutions as the fundamental rights. These rights in Slovakia in case of the print media are guaranteed by the Press Law. The adoption of the law protecting the right to make corrections and the right to reply against the print media was strongly objected by the mass media as well as by the parliamentary political parties belonging to the opposition. The public discussion on the draft of the Press Law was managed in a misleading manner. No attention was paid to many issues of real relevance. Hence, the National Council (the Slovak parliament) approved the law which does not cover the legal status of foreign publishers and press agencies. The enforcement of right to make corrections and the right to reply is poor, if the obliged person ignores the entitled person with his/her requirement for publishing of the correction or the reply. A series of other issues identified within this paper are waiting for a binding interpretation by the competent governmental authorities in the phase of application of the Press Law. It is up to the judiciary within its case-law on right to make corrections and the right to reply.